Health Outcomes for HIV-Infected Persons Released From the New York City Jail System With a Transitional Care-Coordination Plan - Teixeira, Paul A. (Am J Public Health, 2015)
Objectives. We sought to assess 6-month outcomes for HIV-infected people released from New York City jails with a transitional care plan. Methods. Jail detainees in New York City living with HIV who accepted a transitional care plan during incarceration were asked to participate in a multi-site evaluation aimed at improving linkages to community-based care. The evaluation included a 6-month follow-up; HIV surveillance data were used to assess outcomes for those considered lost to follow-up. Results. Participants (n = 434) completed baseline surveys during incarceration in a jail in New York City. Of those seen at 6 months (n = 243), a greater number were taking antiretroviral medications (92.6% vs 55.6%), had improved antiretroviral therapy adherence (93.2% vs 80.7%), and reported significant reductions in emergency department visits (0.20 vs 0.60 visits), unstable housing (4.15% vs 22.4%), and food insecurity (1.67% vs 20.7%) compared with baseline. Conclusions. Transitional care coordination services facilitate continuity of care and improved health outcomes for HIV-positive people released from jail.